Atomic structure of dissociated 60° dislocations in GaAs/GaAs0.92Sb0.08/GaAs heterostructures. (August 2018) - Gangopadhyay, Abhinandan; Maros, Aymeric; Faleev, Nikolai; Smith, David J.
Abstract: Dissociated 60° dislocations in low-misfit GaAs/GaAs0.92 Sb0.08 /GaAs(001) heterostructures are investigated using aberration-corrected scanning transmission electron microscopy. Intrinsic stacking faults bounded by 30° and 90° Shockley partial dislocations are created at the compressively-strained film/substrate interface and the tensile-strained cap/film interface. Unpaired atomic columns are clearly observed at the cores of the 30° partial dislocations for most stacking faults. Comparison with atomic structural models establishes that these dissociated 60° dislocations belong primarily to glide set. For both interface types, the leading partial is located in the constraining layer whereas the trailing partial is located in the layer undergoing strain relaxation. Graphical abstract: Unlabelled Image